High-Resolution Reanalysis of the Mediterranean Sea Biogeochemistry (1999–2019) - Cossarini, Gianpiero; Feudale, Laura; Teruzzi, Anna; Bolzon, Giorgio; Coidessa, Gianluca; Solidoro, Cosimo; Di Biagio, Valeria; Amadio, Carolina; Lazzari, Paolo; Brosich, Alberto; Salon, Stefano (Frontiers in Marine Science, 2021)
Ocean reanalyses integrate models and observations to provide a continuous and consistent reconstruction of past physical and biogeochemical ocean state and variability. We present a reanalysis of the Mediterranean Sea biogeochemistry at 1/24° resolution developed in the Copernicus Marine Environment Monitoring Service (CMEMS) framework. The reanalysis is based on the Biogeochemical Flux Model (BFM) coupled with a variational data assimilation scheme (3DVarBio) and forced by the NEMO-OceanVar physical reanalysis and ECMWF ERA-5 atmospheric fields. Covering the period 1999-2019 with daily means of published and validated 12 biogeochemical state variables, the reanalysis assimilates surface chlorophyll and integrates EMODnet data as initial conditions, World Ocean Atlas (WOA) data at the Atlantic boundary, CO2 atmospheric observations and yearly estimates for riverine nutrients inputs. Using multiple observation sources (remote, in situ and Argo), the quality of the biogeochemical reanalysis was qualitatively and quantitatively assessed with three validation levels that include the evaluation of the 12 state variables and fluxes, and several process-oriented metrics. The results show an overall good skill of the reanalysis in simulating the basin-wide values and variability of the biogeochemical variables. Uncertainty in reproducing observations at mesoscale and weekly temporal scale is satisfactory for chlorophyll, nutrients, oxygen and carbonate system variables in the epipelagic layers, while it increases for few variables (i.e., oxygen, ammonium) in the mesopelagic layers. The vertical dynamics of phytoplankton and nitrate is positively evaluated with BGC-Argo specific metrics. As a consequence of continuous increase of temperature and salinity documented in the Mediterranean Sea in the last 20 years, and of atmospheric CO2 invasion, we observe basin-wide biogeochemical signals reporting surface deoxygenation, increase of alkalinity and DIC concentration, and decrease of pH at surface. The new, high-resolution reanalysis, open and freely available from the Copernicus Marine Service, allows users from different communities to investigate the spatial and temporal variability of 12 biogeochemical variables and fluxes at different scales (from mesoscale to basin-wide and from daily to multi-year) and the interaction between physical and biogeochemical processes shaping the Mediterranean marine ecosystem functioning.